ANALYSIS OF PRODUCT STOCK INVENTORY FORECASTING USING WEIGHTED MOVING AVERAGE METHOD - Anita Rahayu; Arny Lattu; Mupaat Mupaat (Jurnal Teknik Informatika (Jutif), 2022)
A company is said to be successful if it has fulfilled the demands of consumers in the future. cv. Aadiba company is engaged in sales services as a reseller by selling men's outdoor shoes. Problems with the company Cv. Aadiba, which is unable to meet consumer demand because they often experience a shortage of product stock, so far, planning for purchasing product stock is estimated manually based on previous experience and therefore this study aims to predict product stock inventory in order to minimize product stock purchases errors in the future period. and make the implementation of the forecasting system. The method used in the study is the Weighted Moving Average (WMA) method which can estimate the amount of stock that must be purchased for the future period. The data used for this research is sales data from January 2021 to April 2022, the moving average of the previous 3 months. Forecasting results using the Weighted Moving Average (WMA) method produce future sales of 612.5 and the error value of MAD is 104.448718, MSE 28380.712 and the MAPE value is 0.179160773% or 0.18% The smallest error value is considered the most appropriate used for forecasting, then the MAPE value is considered appropriate in forecasting because it has the smallest error value and the implementation of a forecasting system that can facilitate the Cv. Aadiba in terms of forecasting in the future period.